Mobile health applications for children's oral health improvement: A systematic review. (2023) - Mohammadzadeh, Niloofar; Gholamzadeh, Marsa; Zahednamazi, Sorour; Ayyoubzadeh, Seyed Mohammad
Abstract: Background: Oral health is one of the most important components of health that can affect the quality of life of children. Oral problems affect over 600 million children, globally. Evidence showed that mobile-based applications have the potential to facilitate self-care processes for oral health in children. Despite the importance of children's oral health and the role of mobile health in facilitating parental education, few systematic reviews were conducted regarding child oral health and mobile-based applications. Objective: This study aimed to investigate the characteristics and capabilities of m-health applications in children's oral health. Methods: A systematic search was completed using keywords alongside thesaurus and MeSH terms on Web of Science, Scopus, and PubMed databases from 2015 to 2020. The present study was completed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist based on inclusion and exclusion criteria. A synthesis was done to report study findings and patterns identified across studies. All results were analyzed and summarized into general and specific categories. Results: Out of 23 articles included, only nine studies were RCTs (Randomized controlled trials), two studies were cross-sectional studies, one study was evidence-based, and one study was a cluster-randomized trial. According to the findings, most studies were conducted in Brazil, the United Kingdom, and the United States. In terms of the field of dentistry and the application of studies related to dental science, studies fall into three domains, including oral health (61%), orthodontics (4%), and periodontology (26%). Our analysis showed that the developed mobile health applications are equipped with some features to help patients improve their oral health. The most popular features include educational multimedia, game-based stories, reminders, and sending SMS. Conclusion: This study could be the first step towards enhancing our understanding and knowledge regarding applications of mobile health applications in children's oral health. These applications should be developed by involving the end users in the design phase and should be evaluated in terms of usability and effects on the oral health of children.